Preliminary design of single rubber belt with electro-mechanical continuously variable transmission (CVT) - Thong, Yee Han (2010)
An internal combustion engine required transmission system to control or change the transmission ratio between the engine and the drive wheels, so that the vehicle can accelerate constantly. For small power engine such as shooter, the common transmission used is rubber belt continuous variable transmission (CVT). CVT is a kind of transmission that changes the infinite speed ratio between the engine and the drive wheel based on the speed of the engine’s shaft and is known as centrifugal force CVT. Therefore driver cannot control the transmission according to the road profiles needs. To overcome this problem, the mechanism that responsible to change the transmission ratio had to be modified and electro-mechanical CVT is a promising new mechanism that can replace the centrifugal force CVT. In this paper, the new mechanism mixture of mechanical component with electric motor is introduced. Study and analysis are conducted on this mechanism to found out the possibility and potential of improving the current design of CVT. By using theoretical calculation and references from the current CVT design, the new design mechanism is analyzed and verifies the possibility for improvement of the current CVT by using electro-mechanical components to change the transmission ratio.